Increased expression of cysteine cathepsins in ovarian tissue from chickens with ovarian cancer - Ahn Suzie E; Choi Jin; Rengaraj Deivendran; Seo Hee; Lim Whasun; Han Jae; Song Gwonhwa (Reproductive Biology and Endocrinology, 2010)
Abstract Background Cysteine cathepsins (CTSs) are involved in the degradation and remodeling of the extracellular matrix and are associated with cell transformation, differentiation, motility, and adhesion. These functions are also related to cancer cell invasion and metastasis. Chickens spontaneously develop epithelial ovarian cancer and are therefore a good animal model for human ovarian cancer. However, no studies have investigated the expression of CTSs in chickens with ovarian cancer. Methods Cancerous (n = 5) and normal (n = 3) ovaries were collected from 2-to 3-year-old hens, and ovarian tissue samples were collected for study. Ovarian cancers were evaluated with hematoxylin and eosin staining. Reverse transcriptase and quantitative PCR analyses, in situ hybridization analysis were performed to examine the mRNA expression pattern of three CTSs in detail, and protein expression of CTSB was evaluated. Results The CTSB, CTSC, and CTSS genes were highly expressed in cancerous chicken ovaries. Messenger RNAs for the three CTSs were localized to a nodule area, a major characteristic of cancerous ovaries, but the three CTSs showed no specific localization in normal ovaries. Immunoreactive CTSB protein was present in the nodule area of cancerous ovaries. Conclusion Our results suggest that CTSB, CTSC, and CTSS have important functions in the development of epithelial ovarian cancer.